Green fields, safe meals: Applying the fuzzy delphi method to align experts agreement on sustainable agriculture practices in Malaysia - Omar, Mohd Shahir; Yusuf, Muhammad Fakhrul; Cheng, Jack Kie; Rahamaddulla, Syed Radzi; Sorooshian, Shahryar (Asian Journal of Agriculture and Rural Development, 2025)
Rising global food demand and environmental concerns have intensified the need for sustainable agricultural practices that ensure both food safety and long-term productivity. Food safety certification serves as a vital mechanism for promoting sustainable farming by enhancing product quality, market competitiveness, and compliance with international standards. This study examines the determinants influencing Malaysian farmers’ adoption of food safety certification. A systematic literature review identified 35 potential elements, which were subsequently evaluated through expert consensus using the Fuzzy Delphi Method involving 30 agricultural professionals. The analysis validated 22 critical elements encompassing technological, organizational, environmental, and economic dimensions that significantly shape farmers’ adoption decisions. The findings highlight that awareness, perceived market benefits, institutional support, and certification cost are among the most influential drivers and barriers. These results offer strategic insights for policymakers, certification authorities, and agribusiness practitioners in designing targeted interventions to strengthen farmers’ participation in certification programs. The study contributes to a deeper understanding of adoption behavior in Malaysia’s agricultural sector and provides a foundation for enhancing certification uptake in similar emerging economies, ultimately supporting regional food security and sustainable agri-food trade.